Time-Dependent Behavior of a Sessile Water Droplet on Various Papers - AYDEMİR, CEM (TAYLOR & FRANCIS AS, 2010)
In this paper the results of an extensive experimental study on the volume change of a water sessile droplet on various papers such as gloss and matte-coated papers and high-grade papers and boards with certain specifications are reported. The droplet on a paper is observed using a computer-controlled and fully automated instrument. The total volume and the contact angle of the sessile droplet are recorded in short time intervals (as short as 150 milliseconds) for about 6-10min. The evaporation effect on the change of the volume of the water droplet is controlled by measuring the size change of a droplet on a glass surface. The instruments and the material used in the experiments are introduced in detail and the results are displayed in a series of figures and tables. The effects of possible mechanisms on the behavior of the water droplet are discussed, and directions of future studies are indicated. It is concluded that the relationship between water and a cellulose-based substrate cannot be fully understood if the microstructure of the cellulose-based materials and the three main mechanisms, namely evaporation, absorption and hygroexpansion, are not taken into account simultaneously.
Keywords: contact angle; evaporation; hygroexpansion; papers and boards; water absorbency; water-based inks